A Bunch‐like Copper Oxide Nanowire Array as an Efficient, Durable, and Economical Catalyst for the Methanolysis of Ammonia Borane. Issue 4 (5th January 2018) - Cui, Liang; Cao, Xueying; Sun, Xuping; Yang, Wenrong; Liu, Jingquan
Abstract: The dehydrogenation of ammonia borane (AB) is an effective method to produce and store hydrogen, but efficient, durable, and low‐costing dehydrogenation catalysts are lacking. In this work, we successfully prepared a self‐supported bunch‐like copper oxide nanowire array on copper foam (b‐CuO NA/CF) through a facile in situ wet oxidation and annealing method. b‐CuO NA/CF shows high catalytic activity for the methanolysis of AB with an initial turnover frequency of 13.3 mol H 2  molCuO −1  min −1 and an activation energy of 34.7 kJ mol −1 . Moreover, this self‐supported bunch‐like nanoarray catalyst could be easily separated from fuel solutions with excellent stability and maintained its activity even after prolonged use. It is thus an efficient, economical, and durable catalyst for hydrogen fuel cells. Abstract : Pick of the bunch : A bunch‐like CuO nanowire array on copper foam (b‐CuO NA/CF) is obtained by a facile and economical method. This nanowire array behaves as an efficient and durable catalyst for hydrogen generation from the controlled methanolysis of ammonia borane (AB).